MENGATASI KONVERSI BERAGAMA PADAMAHASISWA - Toifur, Toifur (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2011)
Conversion of religion is the term generally given to the process that leads the acceptance of a religious atfitude, the process may occur gradually o r suddenly. Conversion of religion is phenomena that occur among the students. Conversion of religion related with cognitive development of student and getting scientific information process. It can be minimal by peer mediated, critical teaching, and giving a constructive dialogue.